Viewpoints of Dental Students about Practical Value of Educational Contents in Oral Medicine Department - Neda Babaee (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE: For an efficient bedside teaching, the need to investigation, planning and reflection exists. To evaluate the current situation of education system, this study aimed to determine the view of Babol dental students about the practical value of educational contents in oral medicine department. METHODS: In this descriptve and analytical cross-sectional study, a valid and reliable questionnaire was designed. In the 1st part, demographic questions and in the 2nd part, questions about the practical value of theoretical oral medicine contents were asked. The students rated the value as low, moderate and high. The questionnaire was destributed among 101 dental students of 4th, 5th and 6th year . FINDINGS: 90 students full-filled the questionnaires and entered the study. Based on the results of this study, there was no significant difference in the practical value of taught contents among men and women (P=0.596) and also students, method of entrance to dental school (P= 0.413). A significant correlation exists between the practical value of taught contents and their academic year (IV, V, VI)(p<0.05). CONCLUSION: Students mentioned the load of theoretical contents relativaly appropriate to cover clinical needs. 4th year students mentioned the practical values lower than the 5th and 6th year students. Also 5th and 6th year students evaluated the relation of theoretical contents and clinical needs as good which shows desirable correlation and two way communication of theretical and practical contents.